2020
DOI: 10.1093/cdn/nzz139
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Pregnancy History with BMI and Weight Gain in 45–54-Year-Old Women

Abstract: Background Midlife women have a higher risk of cardiometabolic disease than younger women, but the lifelong biological/lifestyle factors responsible for this increase are unclear. Objectives We investigated whether pregnancy history is a risk factor for midlife overweight/obesity and evaluated potential hormonal mechanisms. Methods The Baltimore Midlife Women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…In 2016, 40% of women globally, aged >18 years, were overweight [ 13 ], and women who enter menopause, being overweight or obese, are at great risk for cardiometabolic disruptions [ 14 ]. Metabolic syndrome (MetS) is a cluster of risk factors for CVD, consisting of metabolic abnormalities, such as abdominal obesity, dyslipidemia, hypertension, and hyperglycemia [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, 40% of women globally, aged >18 years, were overweight [ 13 ], and women who enter menopause, being overweight or obese, are at great risk for cardiometabolic disruptions [ 14 ]. Metabolic syndrome (MetS) is a cluster of risk factors for CVD, consisting of metabolic abnormalities, such as abdominal obesity, dyslipidemia, hypertension, and hyperglycemia [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study in middle‐aged retired US women reported that women had a 7% increase in obesity for each additional child born, even after controlling for potential confounders ( 30 ). From a biological point of view, this positive association of parity and obesity can be explained by the numerous metabolic changes that occur during the pregnancy and can persist even after, including insulin resistance and fat accumulation ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate differences in associations between phthalate biomarker concentrations and prior fibroid diagnosis by changes in BMI from age 18 to 45–54 (second objective), we first classified both midlife BMI and BMI at age 18 using the following clinical categories [ 40 ]: under-/normal weight (<25 kg/m 2 ) and overweight/obese (≥25 kg/m 2 ). Then, we categorized changes in BMI as follows: women who remained overweight/obese through age 45–54 (overweight/obese at ages 18 and 45–54), women who became overweight/obese by age 45–54 (under-/normal weight at age 18 but overweight/obese at age 45–54), women who remained under-/normal weight through age 45–54 (under-/normal at ages 18 and 45–54), and those who became under-/normal weight by age 45–54 (overweight/obese at age 18 but under-/normal weight at age 45–54) [ 41 ]. In these models, we included a multiplicative interaction between phthalates and change in BMI to evaluate differences in associations in women who remained overweight/obese through age 45–54, who became overweight/obese by age 45–54, and who remained under-/normal weight.…”
Section: Methodsmentioning
confidence: 99%